A research and policy agenda for the post-pandemic world - Yiu, Chris (Future Healthc J, 2021)
The COVID-19 pandemic response has engaged the academic, public, private and health sectors in the real-time development of technologies and practices to enable predictive, preventive, personalised and participatory (P4) health. Myriad cases of collaborative innovation across these sectors have emerged throughout the pandemic response (despite certain observed technical, social and institutional barriers) that serve as examples to address post-pandemic health system challenges. In this paper, we propose a joint research and policy agenda to generate the knowledge and practices to identify and extend these acute gains toward chronic health system challenges in the post-pandemic era. We identify three key themes for post-pandemic research and policy: the dialectic between novel and traditional techniques, the tension between centralised and local decision-making, and cooperation across academic disciplines, sectors and borders. Going forward, attention to these three themes by researchers and policymakers will help align our health, policy, academic and technological systems to provide better health for all.